Tratamento pós-colheita de goiabas pedro sato com quitosanas - Fráguas, Rodrigo Martins (2016)
Guava is one of the most complete and balanced fruits, with respect to nutritional value. Highly perishable, due to its intense metabolism during ripening, it has a useful life that can reach 3 to 5 days at room temperature. Several methods have been tested to extend the shelf life of this product, since Brazil is currently the world's largest red guava producer. The European market receives the fruit with large acceptance rates, and research in this field has been trying to increase the useful life of this fruit. This study aimed to test edible coatings produced from chitosan. Chitosan is a biopolymer which has shown triple effect in the control treatment of pathogenic microorganisms, activation of various defense responses, inducing and/or inhibiting different biochemical activities during plant-pathogen interactions, and increase in plant storage time, due to filmogenic properties. This study produced and characterized films produced from 3 chitosans, which were kindly provided by Primex. For the production of films, the materials were characterized by gel permeation chromatography, degree of acetylation and thermal analysis. The films were then subjected to thickness analysis, water vapor permeation, amount of solids per square centimeter and apparent strength. Three chitosans with different molecular weights were used, and the films were produced at concentrations of 0.25%, 0.5%, 1% and 1.5% for each chitosan. The results of this study have already been published. With the results of the characterization of films, the concentrations 0.5 and 1%, were chosen, since they had the best results and ease of handling, in addition to satisfactory results in water vapor permeation tests. The guava fruit were then immersed in chitosan solutions, at concentrations of 0.5 and 1%, kept to dry by the peduncle and stored for 8 days at room temperature. The experimental design was completely randomized, and replicates of 9 fruits per treatment were used. The fruits treated with chitosan showed better results for texture, color, firmness, total pectin and soluble pectin, always with lower values than the control fruit.